English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-03-02 03:18:20 · 8 answers · asked by Chirag D 1 in Science & Mathematics Mathematics

8 answers

using the quadratic formula:

y = (1/2)(-19 +- sqrt 97)

2007-03-02 03:21:28 · answer #1 · answered by Mathematica 7 · 0 1

Y^2 + 19Y-66=0

(Y+22) (Y-3)

Y= -22 or Y= 3

2007-03-02 11:30:39 · answer #2 · answered by Anonymous · 1 0

First, we see if we can factor this equation, because if you can, there's no need for the quadratic formula. We see that we can, because in order to factor a trinomial, we have to find the two numbers that multiplied together equal the third number of the trinomial and added together equal the number infront of the second term of the trinomial. Those are 22 and -3 because 22*-3=-66, and 22+-3=22-3=19. And, in both parenthesis, y has to be the first number, and it doesn't matter which parenthesis the 22 goes in and which parenthesis the -3 goes in. Now, knowing all we need to know to factor, we factor.

(y+22)(y-3)=0

Now, we need to use the zero-factor theorem. This theorem is this: Any number multiplied by zero equals zero. So, what we do is first find what number will make the first parenthsis equal to zero. That's -22, because -22+22=0, and it doesn't matter what the other parenthesis is, because any number multiplied by zero is zero. So the first value is -22.
The second value must be 3, because 3-3=0, and it doesn't matter what the first parenthesis is, because any number multiplied by zero equals zero, therefore our second value is 3.
So, we see since we only have two parenthesis, we only have two possible values for this equation by the zero factor theorem. Therefore, our two possible values for y are -22 and 3; so, the answer is:

y= -22,3

There you go. I'm glad I could help. :)

2007-03-02 11:32:59 · answer #3 · answered by iamanicecaringfriend 3 · 1 0

y^2+19y-66=0
(y+22)(y-3)=0
y=-22 and 3

2007-03-02 11:39:11 · answer #4 · answered by Anonymous · 0 0

y² + 19y - 66 = 0

y² + 22y - 3y - 66 = 0

y(y + 22) - 3(y + 22) = 0

(y - 3)(y + 22) = 0

- - - - - -

Roots

y - 3 = 0

y - 3 + 2 = 0 + 3

y = 3

- - - - -

Roots

y + 22 = 0

y + 22 - 22 = 0 - 22

y = - 22

- - - - - - - s-

2007-03-02 11:48:44 · answer #5 · answered by SAMUEL D 7 · 0 0

y2+19y-66=0?
y2+22y-3y-66=0
y(y+22)-3(y+22)=0
(y+22)(y-3)=0
y=3,y=-22

2007-03-02 12:06:26 · answer #6 · answered by kritya s 1 · 1 0

y2+19y-66=0?
y2+22y-3y-66=0
y(y+22)-3(y+22)=0
(y+22)(y-3)=0
y=3,y=-22

2007-03-02 11:22:17 · answer #7 · answered by @"..n"..i"..L 2 · 1 1

approximately .314

2007-03-02 11:31:31 · answer #8 · answered by ajrchops83 1 · 0 1

fedest.com, questions and answers